Comparative outcomes of total wrist arthrodesis for salvage of failed total wrist arthroplasty and primary wrist arthrodesis. (March 2022) - Zijlker, Hero J. A.; Fakkert, Ruben K.; Beumer, Annechien; IJsselstein, Cees B.; Wessels, Mascha; Ritt, Marco J. P. F.
A retrospective study compared outcomes of total wrist arthrodesis as a salvage for total wrist arthroplasty versus primary total wrist arthrodesis. Seventy-one wrists were reviewed after a minimum follow-up of 12 months. Thirty-two wrists with failed total wrist arthroplasty were converted to a wrist arthrodesis and 39 wrists received a primary wrist arthrodesis. Seven converted wrist arthrodeses and five primary arthrodeses failed to fuse. Mean patient-rated wrist and hand evaluation scores and work-related questionnaire for upper extremity disorders scores were 43 and 39 for converted total wrist arthrodesis and 38 and 33 for the primary total wrist arthrodesis. Overall, there were 25 complications in 15 patients in the converted wrist arthrodesis group and 21 complications in 16 patients after a primary wrist arthrodesis. The results between the two groups were slightly in favour of patients with a primary wrist arthrodesis. Therefore, we conclude that the timing, primary or conversion, of total wrist arthrodesis could influence patient outcomes. Level of evidence: III